Das geometrische Nivellement über das grönländische Indlandeis der Gruppe Nivellement A der Internationalen Glaziologischen Grönland Expedition 1967-68. - Seckel, H. (Meddelelser om Grønland, 1977)
During the Summer-Campaign 1968 of EGIG the geometrical levelling of 1959 was repeated. A German group (A) carried out the measurements from the mountains at the western coast of Greenland to the top of the icecap, while a French group (B) started in opposite direction from the eastern coast. In both campaigns the western zone of ablation had to be crossed by levelling on foot; across the icecap the heights were carried by a motorized levelling. The measurements have been controlled by an independent double levelling. The accuracy of the levelling of 1959 and 1968 is similar. As results all the height difierences between the ablation level points and the balises as weil as the heights of each measured point are given.